186 Sleep among Youth During the COVID-19 Pandemic: Differences between Summer and School-Year. (3rd May 2021) - Levenson, Jessica; Ray, Kristin; Lavage, Dan; Wehrer, Edward; Miller, Elizabeth
Abstract: Introduction: Insufficient sleep is highly prevalent among school-age youth and adolescents, which has been exacerbated by the COVID-19 pandemic. However, it is unclear whether sleep during COVID-19 varies based on whether school is in session. We examined the sleep of school-age youth and adolescents during COVID-19 and described changes in rates of insufficient sleep from summer (Time 1) to school year (Time 2). We further examined whether insufficient sleep is associated with mental health service utilization. Methods: Adults in Southwestern Pennsylvania with children under 18 years old in their household completed a repeated cross-sectional electronic survey. The survey was designed to assess usage of, and unmet need for, health and social service resources, among other health behaviors. As responses were anonymous with no longitudinal linking, we used descriptive statistics and Chi-Square tests to examine our aims at each time point. Insufficient sleep was operationalized as <9 hours (school-age youth) and <8 hours (adolescents) of sleep duration, per National Sleep Foundation standards. Results: Data were analyzed from n=97 school-age youth and n=83 adolescents at Time 1, and n=77 school-age youth and n=82 adolescents at Time 2. Most school-age youth (76.3%) obtained sufficient sleep at Time 1, which was maintained at Time 2. However, while 75.6% of adolescents obtained sufficient sleep at Time 1, that number fell to 63.3% at Time 2. Youth with insufficient sleep were more likely to utilize mental health services than those obtaining sufficient sleep at a borderline level of statistical significance (p-value = 0.097), after controlling for age group. Conclusion: The rate of insufficient sleep among adolescents during COVID-19 is meaningfully higher than non-COVID, school-year rates recently reported among adolescents. Youth with insufficient sleep are more likely to utilize mental health services, though the direction of causality in that association is unknown. Future work should focus on strategies for increasing access to sleep promotion programs that support sleep health and mental health during a time of great stress. Support (if any): Supported in part by funding to the Pittsburgh Study (Grable Foundation, Shear Family Foundation, University of Pittsburgh Department of Pediatrics, and UPMC Children's Hospital of Pittsburgh Foundation). Dr. Levenson was supported by K23HD087433.